Community-based disaster management in Kuala Lumpur - Zahari, Rustam Khairi; Raja Ariffin, Raja Noriza (Elsevier, 2013)
The goal of this study is to explore how flood-affected communities in Kuala Lumpur use their community-based organisation (CBO) in dealing with their vulnerability. Data was collected for this study through interviews, survey questionnaire, document analysis and field observation. The study finds CBO has a crucial responsibility in managing disasters affecting their communities especially in ensuring community members are ready for any eventualities and reducing their vulnerabilities. This research also found that the urban poor are the group that is hit the worst in most flooding incidents and the experience that they shared have shaped how they lead their lives.